Synthesis of Nanoporous Rutile Nanocrystals under Mild Conditions. Issue 1721 (9th February 2015) - Sabyrov, Kairat; Yuwono, Virany M.; Penn, R. Lee
ABSTRACT: Single-crystalline rutile with porous and complex structure can be produced by tuning reaction conditions so as to maintain low titania solubility. X-ray diffraction, high-resolution transmission electron microscopy, and cryogenic transmission electron microscopy results are consistent with the hypothesis that oriented aggregation of anatase crystals precedes rutile nucleation and growth from anatase nanocrystal interfaces. The product rutile retains morphological and microstructure features consistent with an aggregation-based phase transformation because coarsening, or monomer-by-monomer growth, is suppressed under these conditions of low titania solubility.